Entrepreneurial networks across oceans to promote international strategic alliances for small businesses - Hara, George; Kanai, Toshihiro (Journal of Business Venturing, 1994)
Alliances with Japanese corporations are generally regarded as difficult and demanding and the literature suggests that there are four reasons for this—general cultural differences; perception and understanding of the legal contract and differences in attitudes to the ways in which this form of arrangement can contribute to organizational learning; the placing of the locus of activities on the value chain; and the effects of global versus multidomestic differences. The article suggests that for small independent firms, the creation of alliances across national boundaries is a social event that relies upon the building and nurturing of a series of entrepreneurial networks. In countries as culturally diverse as Japan and the U.S.A., this may be realized through the use of gatekeepers who facilitate the creation of a “network-of-networks.” The authors analyze the creation of a successful international strategic alliance between the technology-based companies of Kinkel in Japan and three companies in Silicon Valley, U.S.A. None of the four companies are major corporations. From analysis of the case study, the following conclusions are made: 1.1. International strategic alliances between small firms can be more symmetric than those between large and small firms.2.2. Even if national cultures are starkly different, there are common features that characterize technology-based businesses regardless of their country of origin.3.3. Accepting a fit of organizational culture, patience is a key factor of success.4.4. The key to success is a “networker of networks,” a key person or company whose role is to create a global network of local networks.5.5. Social events, such as international symposia, exchange programs, or conventions are important mechanisms for identifying potential partners.6.6. The most important implication of this case study is that the nature of the project will usually require a network of small businesses with different resources.